Application of Stable Isotopes in Aquaculture Nutrition Research - Focken, Ulfert (Avances en Nutrición Acuicola, 2008)
The carbon and nitrogen contained in fish tissue originate from the diet of the animal. The ratio of the stable isotopes (13C/12C, 15N/14N) of the diet is transferred (with a small, but important modification) to the tissue of the fish. Therefore, the analysis of stable isotopes in fish tissues provides information on the isotopic composition of the fish’s diet. This analysis is of special interest in semi-intensive aquaculture systems, in which the growth depends on natural food as well as on compound feed, and in which alternative methods for the study of diet composition are difficult to apply. Other fields for application of this method are the tracing of individual components from a balanced diet in the metabolism of fish, e.g. the tracing of the metabolic fate of different protein (fish meal, plant protein) in fish metabolism.